Gender, Race, Adult Attachment, and Marital Satisfaction Among Malaysians. (April 2013) - Ng, Kok-Mun; Loy, Johnben Teik-Cheok; MohdZain, Zaidy; Cheong, Winnee
This study investigated the gender and race differences on attachment-related avoidance, attachment-related anxiety, and marital satisfaction in the three major Malaysian ethnic groups (i.e., Malays, Chinese, and Indians). Results showed the females reported higher levels of anxiety and lower levels of marital satisfaction than did the males. The Malays were found to report higher levels of anxiety than both the Chinese and Indians. Further regression analyses revealed that anxiety and avoidance were significant predictors of marital satisfaction in the Chinese females, Indian males and females, and Malay males and females while avoidance was the only significant predictor in the Chinese males. Gender and race differences were also observed in the association between attachment and marital satisfaction.